Ganoderma applanatum extract mediated synthesis of silver nanoparticles (Brazilian Journal of Pharmaceutical Sciences, 2023)
Nanotechnology has been used in the field of medicine and pharmacology for its greater efficacy of drug delivery than crude molecules of drugs. In the present study medicinal mushroom Ganoderma applanatum extract mediated silver nanoparticles (AgNPs) were synthesized, characterized by Ultraviolet-visible (UV-Vis.) spectroscopy, scanning electron microscopy (SEM), X-ray diffraction, Dynamic light scattering (DLS) and Furior transform-infrared (FTIR) spectroscopy. Maximum absorbance was recorded at 435nm by UV-Vis. The synthesized nanoparticles of 13.54nm-255nm in size with an average particle size of 58.77nm were analyzed by DLS. FTIR-Spectroscopy provided high transmission at 3606cm-1 corresponds for phenolic capping biochemical. Thus G. applanatum extract can be used for synthesis of silver nanoparticles and the synthesized nanoparticles may be used for development of future therapeutic agent for treatment of diseases.